Shrinking Urban Greenspace and the Rise in Non-communicable Diseases in South Asia: An Urgent Need for an Advocacy - Adhikari, Bipin; Pokharel, Sunil; Mishra, Shiva Raj (Frontiers in Sustainable Cities, 2019)
The burgeoning non-communicable diseases (NCDs) in South Asia in recent decades has changed the morbidity and mortality trends. Among other NCDs, one-third of population in South Asia develops cardiovascular diseases during their lifetime. The rise in NCDs is predicated on multitude of factors such as life-style related behaviours and the increasing urbanization. In recent years, South Asia has seen booming economy, unprecedented amount of rural to urban migration, fast growing urban cities together with decreasing urban green spaces (UGS). Among manifold benefits of UGS such as reducing temperature, noise and improving the air quality, UGS also provides an enabling environment for physical activities, which has been established to reduce the burden of NCDs. In South Asia, although urbanization has apparently improved regional economy, the encroachment and destruction of urban greenspace has put a huge threat to ecological ambience for healthy living which can contribute to rising burden of NCDs and consequently lead to huge economic loss. We draw on literature and our regional perspective to advocate the need for sustainable urban green cities by exploring the impact of urban green space on NCDs.